2020
DOI: 10.26496/bjz.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in livers of raptors from Eastern Poland – the importance of diet composition

Abstract: Concentrations of Pb, Cd, Ni, Cr and Hg were determined in livers of six species of raptors collected in the area of Eastern Poland. Redundancy analysis (RDA) showed that elevated Hg and Cr concentrations were directly related to feeding on passerines. Raptors that specialised in seizing small mammals as a source of food revealed higher hepatic concentrations of Pb and Cd in comparison with other raptors. Unlike Cd, we found statistically significant differences in the Pb concentrations in livers of Common buz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Within our study, Hg was detected with the highest concentration in S. uralensis (Ural owl), with a median value of 213 ppb ww in livers and 120 ppb ww in muscles (Table 2). Comparing our results with other European researches, Kitowski et al ( 2016) in Poland revealed a significantly higher average hepatic concentration of mercury in sparrowhawks (666 ppb ww), with the highest individual level of 3 996 ppb ww, if compared with kestrels (mean value 213 ppb ww) and common buzzards (211 ppb ww) [29]. The authors, based on Redundancy analysis, showed that higher concentrations of mercury in livers of sparrowhawks are strongly dependent on the consummation of small granivorous birds (such as passerines) feeding on grains illegally treated with Hg-based fungicide what was confirmed also in monitoring carried out in Hungary [30].…”
Section: Mercury (Hg)supporting
confidence: 81%
See 1 more Smart Citation
“…Within our study, Hg was detected with the highest concentration in S. uralensis (Ural owl), with a median value of 213 ppb ww in livers and 120 ppb ww in muscles (Table 2). Comparing our results with other European researches, Kitowski et al ( 2016) in Poland revealed a significantly higher average hepatic concentration of mercury in sparrowhawks (666 ppb ww), with the highest individual level of 3 996 ppb ww, if compared with kestrels (mean value 213 ppb ww) and common buzzards (211 ppb ww) [29]. The authors, based on Redundancy analysis, showed that higher concentrations of mercury in livers of sparrowhawks are strongly dependent on the consummation of small granivorous birds (such as passerines) feeding on grains illegally treated with Hg-based fungicide what was confirmed also in monitoring carried out in Hungary [30].…”
Section: Mercury (Hg)supporting
confidence: 81%
“…For instance, in Poland, Kitowski et al revealed mean concentration of Cd in livers of raptors ranged between 282 and 786 ppb dw with a maximum value of 3 425 ppb dw (1 141 ppb ww after conversion) in one common buzzard. Contrary, in other species of birds of prey much lower cadmium concentrations were measured [29,31]. Also, in another recent study, Kanstrup et al (2019) revealed significantly higher cadmium concentrations in livers of common buzzards and tawny owls than in kestrels, goshawks and white tailed eagles [32].…”
Section: Cadmium (Cd)mentioning
confidence: 87%
“…Isotopic analysis was consistent with lead ammunition. One bird that died in 2013 had a lead bullet in the stomach and a liver lead of 36.3 ppm wwIshii et al (2017)Common buzzard Buteo buteo PortugalAuthors reported an apparent association between PbB and the hunting seasonCarneiro et al (2014)PolandForaging on carrion and game carcasses was associated with elevated (> 6 ppm dw) liver Pb concentrations in some buzzards; 3 of 31 birds taken to rehabilitation centres that later died had liver Pb > 6 ppm dw with one bird exceeding 15 ppm dwKitowski et al (2016)Southern ground hornbill a Bucorvus leadbeateri Authors reported acute lead poisoning in a bird. Lead particles in the gizzard were probably from the carcass of a porcupine ( Erethizon dorsatum ) that was killed with lead shot.…”
Section: Pathways Of Exposurementioning
confidence: 99%
“…Accumulation of toxic metals in feedstuffs destined for human or livestock animal consumption can be easily checked and monitored whereas the diet of wild animals is almost impossible to regulate. Heavy metals have been shown to accumulate in kidney, liver, blood, feathers, eggs and bones (Burger and Gochfeld 1993; Fasola et al 1998; Mateo and Guitart 2003; Deng et al 2007; Jayakumar and Muralidharan 2011; Farahani et al 2015; Kitowski et al 2016; Zarrintab and Mirzaei 2018).…”
Section: Introductionmentioning
confidence: 99%